Anaplastic large cell lymphoma-propagating cells are detectable by side population analysis and possess an expression profile reflective of a primitive origin - Moti, Naushad; Merkel, Olaf (Oncogene, 2015)
Cancer stem cells or tumour-propagating cells (TPCs) have been identified for a number of cancers, but data pertaining to their existence in lymphoma so far remain elusive. We show for the first time that a small subset of cells purified from human anaplastic lymphoma kinase (ALK)-positive and -negative, anaplastic large cell lymphoma cell lines and primary patient tumours using the side population (SP) technique have serial tumour-propagating capacity both in vitro and in vivo; they give rise to both themselves and the bulk tumour population as well as supporting growth of the latter through the production of soluble factors. In vivo serial dilution assays utilising a variety of model systems inclusive of human cell lines, primary human tumours and nucleophosmin (NPM)-ALK-induced murine tumours demonstrate the TPC frequency to vary from as many as 1/54 to 1/1336 tumour cells. In addition, the SP cells express higher levels of pluripotency-associated transcription factors and are enriched for a gene expression profile consistent with early thymic progenitors. Finally, our data show that the SP cells express higher levels of the NPM-ALK oncogene and are sensitive to an ALK inhibitor.